The Origins of Reformed Discourse on Imputed Active Obedience: Heidelberg’s Reception of Georg Karg's 100 Propositions on Justification in 1565 - McDaniel, Matthew C. (Reformation & Renaissance review, 2025)
Where and when did Reformed theologians first debate the imputed active obedience of Christ (IAOC)? Through previously overlooked correspondence, this article establishes that Reformed discourse on IAOC originated in spring 1565 when Heidelberg theologians Zacharias Ursinus and Caspar Olevianus favourably received Georg Karg's propositions, prompting concern from Heinrich Bullinger and Theodore Beza about potential division. The study documents how Reformed authorities resolved this controversy by 1570, designating the IAOC as adiaphora – permitting both pro – and contra-IAOC positions among the Reformed. This resolution, advocated particularly by Ursinus and Bullinger, prioritised ecclesial unity over doctrinal precision. The findings upend narratives of an early Reformed consensus on the IAOC, revealing instead theological diversity from the doctrine's inception. The article provides a chronological anchor for understanding early Reformed orthodox development and demonstrates the conscious coexistence of divergent views on the IAOC.